Pengaruh Penggunaan Model Pembelajaran Realistic Mathematics Education (RME) terhadap hasil belajar siswa pada pokok bahasan teorema phytagoras di Madrasah Tsanawiyah - Pakhrurrozi, Imam (LP2M STAI Darul Kamal NW Kembang Kerang, 2021)
Abstract Issues about learning mathematics associated with everyday life have attracted the attention of researchers and educators. Learning that emphasizes the daily experiences of students more easily understands learning material and has a strong memory in applying mathematics in real life as the dependent variable in the form of children's learning achievement. This article aims to re-examine whether learning realistic mathematics (Realistic Mathematics Education) has an influence on student achievement. Using a quasi-experimental research method, the population is all students of class VIII MTS NW SIKUR, a total of 50 students consisting of class 25 students in class VIII A and 25 students in class B. Data was collected through a test technique and analyzed according to data analysis procedures. The findings of this study are there is the influence of the learning model of the Realistic Mathematics Education (RME) learning model in improving student learning outcomes in mathematics on the Pythagorean theorem material for Madrasah Tsanawiyah students